Contrasting roles of histone 3 lysine 27 demethylases in acute lymphoblastic leukaemia - Ntziachristos, Panagiotis; Tsirigos, Aristotelis; Welstead, G. Grant; Trimarchi, Thomas; Bakogianni, Sofia; Xu, Luyao; Loizou, Evangelia; Holmfeldt, Linda; Strikoudis, Alexandros; King, Bryan; Mullenders, Jasper; Becksfort, Jared; et al. (Nature (London), 2014)
T-cell acute lymphoblastic leukaemia (T-ALL) is a haematological malignancy with a poor prognosis and no available targeted therapies; now two histone H3 lysine 27 demethylases, JMJD3 and UTX, are shown to have contrasting roles in human T-ALL cells and a mouse model of the disease, and a small molecule demethylase inhibitor is found to inhibit the growth of T-ALL cell lines, introducing a potential therapeutic avenue for acute leukaemia. Targeting acute lymphoblastic leukaemia Two histone H3 lysine 27 demethylases, JMJD3 and UTX, are shown here to have contrasting roles in human T-cell acute lymphoblastic leukaemia (T-ALL) cells and a mouse model of the disease. JMJD3 is overexpressed in T-ALL and essential for initiation and maintenance of disease, whereas UTX is a target of inactivating mutations in human T-ALL and acts a tumour suppressor. A small-molecule demethylase inhibitor inhibits the growth of T-ALL cell lines, introducing a potential therapeutic avenue for an acute leukemia that has a poor prognosis and no currently available targeted therapies. T-cell acute lymphoblastic leukaemia (T-ALL) is a haematological malignancy with a dismal overall prognosis, including a relapse rate of up to 25%, mainly because of the lack of non-cytotoxic targeted therapy options. Drugs that target the function of key epigenetic factors have been approved in the context of haematopoietic disorders 1 , and mutations that affect chromatin modulators in a variety of leukaemias have recently been identified 2 , 3 ; however, ‘epigenetic’ drugs are not currently used for T-ALL treatment. Recently, we described that the polycomb repressive complex 2 (PRC2) has a tumour-suppressor role in T-ALL 4 . Here we delineated the role of the histone 3 lysine 27 (H3K27) demethylases JMJD3 and UTX in T-ALL. We show that JMJD3 is essential for the initiation and maintenance of T-ALL, as it controls important oncogenic gene targets by modulating H3K27 methylation. By contrast, we found that UTX functions as a tumour suppressor and is frequently genetically inactivated in T-ALL. Moreover, we demonstrated that the small molecule inhibitor GSKJ4 (ref. 5 ) affects T-ALL growth, by targeting JMJD3 activity. These findings show that two proteins with a similar enzymatic function can have opposing roles in the context of the same disease, paving the way for treating haematopoietic malignancies with a new category of epigenetic inhibitors.